Disposal practices of unwanted household medications in China: a cross-sectional study - Bin Jiang; Weiqi Chen; Yaoguang Zhang; Zhao Yang; Zhixin Liu; Xing Lin Feng; Qiyun Zhu; Qingyuan Xue (BMJ Open)
Objectives This study aimed to understand disposal practices of unwanted medications in Chinese households and examine associations between influencing factors and these disposal practices.Design A nationwide cross-sectional study conducted between 11 October and 26 October 2018.Setting Municipalities directly under the central government and provincial capitals across 30 provinces and autonomous regions.Participants A total of 6293 households participated in the study.Primary and secondary outcome measures A self-designed questionnaire was used to survey disposing methods of unwanted medications, which were categorised into three groups: household waste disposal, recycling and use or give unwanted medications to others.Results 2771 (44%) households reported they have unwanted medications. The majority (89%) disposed of unwanted medications in the bin, sink or toilet. Having a family member of 65 years old and above (OR: 5.45; 95% CI: 3.20 to 9.26), having a family member of medical professions (OR: 1.45; 95% CI: 1.15 to 1.83), receiving information on proper disposal (OR: 6.03; 95% CI: 4.54 to 8.00) and having a high level of perception of risk to the environment (OR: 1.56; 95% CI: 1.05 to 2.30) were associated with recycling. Additionally, a household having more than 10 medications stored (OR: 1.73; 95% CI: 1.29 to 2.34) was more likely to dispose of unwanted medications in the bin or sink/toilet. Women were less likely to use unwanted medications or give them to others (OR: 0.59; 95% CI: 0.38 to 0.90). A higher perception of health risks was associated with increased recycling, particularly among middle-aged and older adults (OR: 1.60; 95% CI: 1.04 to 2.47) and decreased likelihood of using unwanted medications or giving them to others (OR: 0.36; 95% CI: 0.20 to 0.67).Conclusions There is an urgent need to establish a standardised management system for rational disposal of unwanted medications in China. This system should aim to promote and educate the public on rational stocking and use of medications, as well as appropriate disposal practices.